Enhancing menstrual hygiene management: an evaluation of knowledge, practices, and university support among female students at UiTM - Lee, Noor Azli Affendy; Abd Ghani, Kay Dora; Rozli @ Rosli, Mohd Ikmal Fazlan; Sulaiman, Suria; Zaini, Intan Rabiatulainie (Universiti Teknologi MARA, Kedah, 2025)
This study investigates the knowledge, perceptions, and support systems related to female hygiene among students at Universiti Teknologi MARA (UiTM). Conducted through a survey of 173 female students, the research explores various aspects of menstrual hygiene management (MHM), including the availability of hygiene products, personal practices, and the impact of menstrual health on academic performance. The findings reveal a moderate level of self-assessed knowledge about female hygiene, with significant gaps in formal education on the subject. Access to hygiene products emerged as a challenge, with cost and availability cited as major barriers. The study also highlights the stigma surrounding menstruation, with students expressing strong support for initiatives aimed at breaking this stigma and promoting open discussions about menstrual health. The qualitative data suggest the need for universities to improve restroom facilities, provide free or affordable hygiene products, and implement educational programs to better support female students. The study underscores the importance of addressing these needs to create a more inclusive and supportive campus environment that enhances the well-being and academic success of female students.